Examining Customer Loyalty and Retention as Drivers of Satisfaction in Internet Banking - Monika Dahiya; Dr. Mahipal Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The rapid evolution of digital technologies has revolutionized the banking industry, making internet banking a key financial service globally. In India, increasing smartphone penetration and internet accessibility have accelerated the adoption of digital banking, particularly in regions like Haryana, where customers exhibit diverse banking behaviors across urban and rural demographics. This study examines the role of customer loyalty and retention as primary drivers of customer satisfaction in internet banking. The research investigates how customer engagement, security perceptions, and service efficiency influence long-term digital banking adoption. A survey-based quantitative approach was used to analyze responses from 600 internet banking users in Haryana. The study employed correlation analysis, t-tests, and regression models to evaluate relationships between customer satisfaction, loyalty, and retention, while also assessing the impact of demographic factors such as age, education, and location. Results indicate a strong positive association between loyalty and satisfaction (r = 0.372, p < 0.01), confirming that satisfied users are more likely to remain loyal to their banking platform. Additionally, transaction security was found to be a significant determinant of retention (r = 0.116, p < 0.01), emphasizing the need for robust security protocols. The study highlights that rural users report lower satisfaction with security and reliability compared to urban users, pointing to the need for localized digital literacy initiatives and enhanced cybersecurity measures. Banks must adopt targeted engagement strategies to improve user experience and foster long-term loyalty. The findings provide valuable insights for financial institutions to refine their customer retention models, ensuring sustainable digital banking adoption in India's evolving fintech landscape.
Keywords: Customer Loyalty; Retention; Satisfaction; Internet Banking; Digital Banking; India; Rural-Urban; User Engagement